Pengaruh Pengembangan Karir, Lingkungan Kerja, Serta Apresiasi Pimpinan Terhadap Tingkat Kepuasan Kerja Karyawan Di Departemen Human Capital PT Biofarma - Duana, Refiza Gita; Ismail, Gurawan Dayona (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
This study aims to examine the relationship between career development, work environment, and leadership appreciation toward employee job satisfaction in the Human Capital Service Division of PT Bio Farma. Data were collected through a closed-ended Likert-scale questionnaire distributed to 40 respondents. The research instrument was tested for validity and reliability prior to analysis using multiple linear regression. The results indicate that both the work environment and leadership appreciation have a significant influence on job satisfaction, whereas career development does not show a significant effect. Simultaneously, the three independent variables contribute significantly to job satisfaction, with a coefficient of determination (R²) of 0.413. This finding implies that over 40% of the variation in job satisfaction can be explained by the three variables. The study highlights the importance of developing human resource policies that emphasize a supportive work environment and an effective, fair recognition system.